Study on optimal impact damper using collision of vibrators. (20th January 2016) - Iwata, Yoshio; Komatsuzaki, Toshihiko; Kitayama, Satoshi; Takasaki, Tatsuya
Abstract: In this paper, we propose an impact damper which consists of multiple vibrators installed on a main structure and dissipates the vibrational energy by collisions between the vibrators. Transient vibration of the main system subject to an impact rapidly converges to zero by the impact damper. DE (Differential Evolution) method which is one of the optimization methods is employed to determine mass and spring constant of the every vibrators to maximize damping effect. We discuss the effect of a coefficient of restitution of vibrators, a ratio of total mass of the vibrators to the main structure mass and the number of the vibrators on the damping performance. The damping effect of the impact damper with three vibrators is demonstrated experimentally.